Therapeutic potential and pharmacological insights of total glucosides of paeony in dermatologic diseases: a comprehensive review - Wang, Huige; Yu, Wenchao; Wang, Tong; Fang, Dianwei; Wang, Zeyun; Wang, Yuanhong (Frontiers in Pharmacology, 2025)
Total glucosides of paeony (TGP) are a group of monoterpenes extracted from Paeonia lactiflora Pall., primarily including metabolites such as paeoniflorin and oxypaeoniflorin. Modern pharmacological studies have shown that TGP possesses a variety of biological effects, including immunomodulatory, anti-inflammatory, hepatoprotective, nephroprotective, antidepressant, and cell proliferation regulatory activities. In recent years, clinical research has demonstrated favorable therapeutic effects of TGP on disorders of the liver, cardiovascular, nervous, endocrine, and skeletal systems. Particularly in dermatological treatments, TGP has been found to significantly improve clinical symptoms and shorten the course of the disease. However, there are still certain limitations in the scientific rigor of existing studies and in its clinical application. To assess the potential of TGP in treating dermatologic diseases, this article provides a review of its botanical sources, preparation and extraction processes, quality control, and major chemical metabolites, as well as its pharmacological research and clinical applications in dermatology. Additionally, the mechanisms of action, research gaps, and future directions for TGP in the treatment of dermatologic diseases are discussed, offering valuable guidance for future clinical research on TGP in dermatology.